Canada and the challenges of international development and globalization - Masaeli, Mahmoud, 1954-; Munro, Lauchlan T., 1961- (Studies in international development and globalization., 2018)
"What are Canada's various links with international development and globalization? They extend beyond foreign aid to diplomacy, trade, finance, aid, immigration, military intervention (both peacekeeping and combat roles), membership in a variety of international organisations, and people-to-people links. This multi-disciplinary and multi-author textbook, designed for first- or second-year students, introduces the main concepts, ideas, theories, and perspectives that form the historical background and foundation of Canada's interactions with developing countries in a globalizing world. It discusses Canada's diplomacy vis-à-vis developing countries and changes in priorities over time. It examines Canada's political, economic, military, social, immigration and aid policies and how they have interacted with each other. It presents economic, political, and cultural dimensions of the process of globalization and the ways they affect Canada; examines the public development institutions and policies, private sector and civil society organizations in Canada; and explores the moral imperatives behind Canadian international policy. Finally, it examines current issues, including Canada's promotion of human rights, democracy, good governance, support to the private sector, relations with fragile states, and relations with the emerging economies. Each thematic chapter is written by a different subject matter expert and is supplemented by case studies of issues and incidents, following a common template. The case studies, also written by different subject matter experts, also follow a common template. Each case study is designed to be read in conjunction with two or more thematic chapters."--